FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU CUCI TANGAN PAKAI SABUN PADA SISWA DN DI KECAMATAN SIMPANG PEMATANG KABUPATEN MESUJI PROVINSI LAMPUNG - Livana Bahri (Jurnal Ilmu Kesehatan Masyarakat Indonesia (JIKMI), 2020)
AbstractThe effectiveness of CTPS on reducing the incidence of diarrhea is 44%, this is evidenced by the 2013 Riskesdas data which shows that the prevalence of Riskesdas 2013 (3.5%) is smaller than the Riskesdas 2007 (9.0%). CTPS campaign six times during 2008-2013. This research aims to find out the factors related to the behavior of washing hands with soap in SDN students in Simpang Pematang District, Mesuji Regency, Lampung Province in 2017. This type of research is a quantitative survey. The research design used is cross-sectional. The study population is the population in this study is the fifth grade elementary school students in Simpang Pematang District totaling 263 students. And the sample is 184 respondents with proportional random sampling technique. Data analysis using univariate, bivariate with chi-square test. The results of the research analysis showed that there was no significant relationship between sexes (p-value = 0.547). There is a relationship of knowledge (p-value = 0,000), attitude (p-value = 0.008), perception (p-value = 0.004), information exposure (p-value = 0,000), officer support (p-value = 0.007), teacher support (p-value = 0,000), family support (p-value = 0.009). This study suggests that officers provide counseling to respondents and counseling to the community, and are also expected to be a source of information for the community so that it can increase knowledge and awareness of health and can be positive towards everything something related to a disease that can be prevented by washing hands. Keywords: Factors, Hand Washing Behavior